2012
DOI: 10.1038/tp.2012.32
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for biological roots in the transgenerational transmission of intimate partner violence

Abstract: Intimate partner violence is a ubiquitous and devastating phenomenon for which effective interventions and a clear etiological understanding are still lacking. A major risk factor for violence perpetration is childhood exposure to violence, prompting the proposal that social learning is a major contributor to the transgenerational transmission of violence. Using an animal model devoid of human cultural factors, we showed that male rats became highly aggressive against their female partners as adults after expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 46 publications
3
63
1
1
Order By: Relevance
“…Existing evidence has identified alterations in the CRH system accompanying certain psychopathologies (Holsboer and Ising, 2008;Binder and Nemeroff, 2010) such as anxiety and depression, linked to early life adversity (Coplan et al, 1996;Nemeroff, 2004;Avital and Richter-Levin, 2005;Schmidt et al, 2007;Heim et al, 2008;Cordero et al, 2012). Although drug treatments tackling CRHR1 have been envisioned as potentially promising anxiolytic and antidepressive drugs (Kunzel et al, 2003;Refojo and Holsboer, 2009), recent evidence in rodents suggests that they could also be effective in modifying not only actual pathological manifestations at adulthood but also the developmental trajectories linking early adversity to adult psychopathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing evidence has identified alterations in the CRH system accompanying certain psychopathologies (Holsboer and Ising, 2008;Binder and Nemeroff, 2010) such as anxiety and depression, linked to early life adversity (Coplan et al, 1996;Nemeroff, 2004;Avital and Richter-Levin, 2005;Schmidt et al, 2007;Heim et al, 2008;Cordero et al, 2012). Although drug treatments tackling CRHR1 have been envisioned as potentially promising anxiolytic and antidepressive drugs (Kunzel et al, 2003;Refojo and Holsboer, 2009), recent evidence in rodents suggests that they could also be effective in modifying not only actual pathological manifestations at adulthood but also the developmental trajectories linking early adversity to adult psychopathology.…”
Section: Discussionmentioning
confidence: 99%
“…The peripubertal period is a biological transitional phase involving adaptations in hormonal systems and neural circuits, including those related to stress and the development of emotionality (Spear, 2009;Romeo, 2010). In our lab, exposure of rats to stressful experiences (e.g., synthetic fox odor and exposure to an elevated platform) on scattered days during the peripuberty period (P28eP30, P34, P36, P40 and P42) was found to induce long-lasting effects on anxiety and stress-coping behaviors, including deficits in social behaviors (Toledo-Rodriguez and Sandi, 2011;Cordero et al, 2012;Marquez et al, 2013), as well as changes in metabolic responses in limbic brain regions including the hippocampus and the amygdala (Toledo-Rodriguez et al, 2012;Marquez et al, 2013). Here, we sought to investigate whether peripuberty stress would lead to alterations in the CRH system in limbic areas and whether pharmacological treatment with a CRHR1 antagonist during the immediate post-stress developmental period (i.e., adolescence) would reverse the long-term behavioral consequences of peripuberty stress.…”
Section: Introductionmentioning
confidence: 92%
“…We have previously shown that male rats submitted to stress -consisting of fear-inducing experiences -during the peripuberty period display as adults abnormal aggressive behavior against both male intruders (Marquez et al, 2013) and female partners (Cordero et al, 2012). In the present study, we examined whether the same stress protocol would affect the development of aggressive behaviors in female rats exposed to stress experiences during puberty.…”
Section: Introductionmentioning
confidence: 91%
“…This arousing experience stimulates social interactions and for this reason, it was used as the starting time for behavioral observations (Cordero et al, 2012). The first time each female and male were put together in the home-cage, and the periods immediately following homecage changing on days 9 and 18, were video-recorded for 10 min.…”
Section: Behavior During Cohabitation With Male Partnersmentioning
confidence: 99%
See 1 more Smart Citation